Resolution of Coccidioides immitis Endophthalmitis with an Aggressive Surgical and Medical Therapeutic Approach. (July 2013) - Reed, David C.; Shah, Kayur H.; Hubschman, Jean-Pierre
Abstract Introduction: Coccidioides immitis endophthalmitis usually results in enucleation, and there is evidence that vitrectomized eyes are more likely to become enucleated. Methods: A 55-year-old man presented to us with steroid-resistant granulomatous uveitis and was eventually diagnosed with C. immitis endophthalmitis. He was treated with an aggressive medical and surgical approach, receiving a total of 16 intravitreal antifungal injections and three vitrectomies, as well as lensectomy and penetrating keratoplasty. Results: At 13 months after presentation, the patient's eye was free of inflammation, and his best corrected visual acuity was 20/25. Discussion: This is the first reported case of culture-proven C. immitis endophthalmitis with a favorable final outcome. We propose that the good outcome may have been due to our aggressive therapeutic approach.